Hubungan Dukungan Sosial Perawat dengan Mekanisme Koping Keluarga Pasien di Rumah Sakit Santa Elisabeth Medan - Derang, Imelda; Saragih, Helinida; Br. Sinulingga, Chindy Kalista (JURNAL KEPERAWATAN MERSI, 2023)
Background: Nurses provide social support to the patient's family in the intensive care unit in the form of emotional and informational support through communication about developments in the condition of family members. Good social support will form coping mechanisms so that each individual was able to adapt to the situation they were experiencing and can help the process. Social support also makes a person feel cared for, respected, and loved. It was utilized to give care and healing for sick family members. Objective: The aim of this study was to investigate the relationship between nurses' social support and the coping mechanisms of the patient's family. Methods: A cross-sectional study was undertaken at Santa Elisabeth Hospital Medan. 36 samples were taken using an accidental sampling technique. The data was analyzed using Spearman rank.Â  Results: 29 respondents (80.6%) fulfilled social support from nurses, 7 respondents (19.4%) do not fulfill it, 27 respondents (75.0%) adaptive coping, 9 respondents (25.0%) maladaptive coping. The correlation between the social support of nurses and the coping mechanisms of families of intensive care unit patients is significant, as indicated by the Spearman rank test results with a p value = 0.000 (p <0.05). The correlation coefficient is 0.851**, indicating a very strong level of relationship strength between the nurse's social support variable and the coping mechanism. Conclusion: Further study can be conducted in inpatient rooms and other locations.